An intelligent curve warning system for road cycling races - Zignoli, A. (Sports Engineering, 2021)
To mitigate the incidence of the crashes in road cycling races, new technologies that can help the riders in evaluating risks in advance are called for. An advanced rider assistance system has been developed to warn the riders before they negotiate a corner during a fast-descending section. The advanced rider assistance system was based on the optimal manoeuvre method applied to a state-of-the-art cycling locomotion model. Global positioning system data collected at 1 Hz were used to compute initial conditions for the optimal manoeuvre calculation. The advanced rider assistance system was deployed on a mobile device, and it was tested off-line for real-time performances. Computational cost was examined versus the horizon length to arrive at an optimum for the problem. The proposed advanced rider assistance system was designed to provide audible warning to the riders so they can focus their actions and improve trajectory security. This work prompts more research to reduce the incidence of crashes in cycling training and racing by means of new methods based on optimal manoeuvre calculation.